Dietary implications of supermarket development: A global perspective - Hawkes, Corinna (Wiley, 2008)
Five decisions by supermarket operators have important dietary implications: the location of their outlets; the foods they sell; the prices they charge; the promotional strategies they use; and the nutrition‐related activities they implement. These decisions influence food accessibility, availability, prices and desirability, which in turn influence the decisions consumers make about food. Based on a comprehensive literature review, this article finds that the dietary implications are both positive – supermarkets can make a more diverse diet available and accessible to more people – and negative – supermarkets can reduce the ability of marginalised populations to purchase a high‐quality diet, and encourage the consumption of energy‐dense, nutrient‐poor highly‐processed foods. Overall, the most universally applicable dietary implication is that supermarkets encourage consumers to eat more, whatever the food.